Global Market Reaction to the Indonesian Islamic Capital Market During Covid Outbreak - Ahmad Habibi; Khavid Normasyhuri; Aula Nurul Ma'rifah (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2023)
The COVID-19 pandemic has impacted the global Islamic capital market, including Indonesia. As a result, it is critical to investigate the global stock market reaction to this issue. This study seeks to comprehend the global Islamic stock market's reaction to the Indonesian Islamic stock market, as represented by the Jakarta Islamic Index (JII), during the COVID-19 outbreak. To test the hypothesis, this study employs the Error Correction Model (ECM) techniques. The findings revealed that the global Islamic stock market had a significant influence on the Indonesian Islamic stock market during that time, both in the short and long term. This is due to the Islamic stock market's interconnected nature, which attracts investors as it allows foreigners to own Islamic stocks in Indonesia, and also offers valuable long- and short-term prospects. In addition, the globalization of the world economy, social and political relations are interrelated between countries, especially in the era of COVID-19. Because the outbreak was unavoidable, it caused global economic chaos and extreme crises, including investments in the Islamic stock market. In light of crisis, the findings of this study can be used as practical guidance for investors considering investing in the Islamic stock market.============================================================================================================== ABSTRAK - Reaksi Pasar Global Terhadap Pasar Modal Syariah Indonesia Dalam Masa Covid-19. Pandemi COVID-19 berdampak pada pasar modal syariah global, termasuk Indonesia. Oleh karena itu, kajian yang berkaitan dengan hal tersebut sangat penting dilakukan. Penelitian ini bertujuan untuk mengkaji reaksi pasar modal syariah global terhadap pasar modal syariah Indonesia yang diwakili oleh Jakarta Islamic Index (JII) dalam masa COVID-19. Untuk menguji hipotesis, penelitian ini menggunakan teknik Error Correction Model (ECM). Hasil temuan menunjukkan bahwa pasar modal syariah global memiliki pengaruh signifikan terhadap pasar modal syariah Indonesia, baik dalam jangka pendek maupun jangka panjang. Hal ini disebabkan oleh sifat interkoneksi pasar modal syariah, yang menarik investor karena memungkinkan orang asing untuk memiliki saham syariah di Indonesia, dan juga menawarkan prospek jangka panjang dan jangka pendek yang menguntungkan. Selain itu, akibat globalisasi ekonomi, hubungan sosial dan politik antar negara saling berkaitan, terutama di era COVID-19. Karena pandemi tersebut tidak terhindarkan, kondisi ekonomi global dan krisis terjadi dalam berbagai sektor, termasuk pasar modal syariah. Temuan penelitian ini berimplikasi sebagai pedoman praktis bagi investor dalam berinvestasi di pasar modal syariah di Indonesia.